A Personal Perspective on Legislation: Northern Milk Revisited – Soured or Still Fresh? - White, Douglas (Victoria University of Wellington Law Review, 2016)
The thesis of this article is that the overarching objective of statutory interpretation is to "make the Act work" as the Court of Appeal held in Northern Milk. This requires a common sense and practical approach. The article demonstrates the thesis by reference to subsequent Court of Appeal decisions and the complementary legislation establishing the Law Commission and the Parliamentary Counsel Office. The issues raised by the Law Commission’s recently reactivated reference on the law of contempt of court are considered by way of example. The conclusion is that the Northern Milk approach remains apposite.